Podcast as an educational technology for seniors and their caregivers: an experience report (Research, Society and Development, 2022)
This article aims to describe the use of podcasts as an educational technology for seniors and their caregivers. It is a proposal for an experience report, with a descriptive qualitative approach, with a view to disseminating relevant information for the elderly and their caregivers, developed in the extension project of the Aurora de Afonso Costa School of Nursing by the Dean of Extension at the Federal Fluminense University. This article is based on the following discussions: the importance of the support network for caregivers of the elderly; guidance on the elderly during the Covid-19 Pandemic period, with an emphasis on vaccination and the podcast as educational technology for seniors and their caregivers. This technology enables an understanding of elderly people experienced in daily life in order to enable the improvement of care developed aiming at quality of life, especially during the Covid-19 pandemic, thus making essential information for the health of the old man. Therefore, the use of podcasts as an educational technology has a proposal to inform and communicate outstanding issues for the elderly, caregivers and family members, being a tool that allows us to offer content related to the health of this elderly person and their caregivers.